2018
DOI: 10.1016/j.bbmt.2018.03.018
|View full text |Cite
|
Sign up to set email alerts
|

De-Escalation and Discontinuation of Empirical Antibiotic Treatment in a Cohort of Allogeneic Hematopoietic Stem Cell Transplantation Recipients during the Pre-Engraftment Period

Abstract: To investigate rates and outcomes of antibiotic de-escalation during pre-engraftment neutropenia in allogeneic hematopoietic stem cell transplantation (HSCT) recipients. 110 consecutive HSCTs performed between January 2013 and March 2014 were analyzed. De-escalation was defined as narrowing the spectrum of antibiotic treatment either within (early) or after 96 hours (late) from starting antibiotics. Discontinuation, considered a form of de-escalation, was defined as stopping antibiotics before engraftment. De-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…The management of febrile neutropenia in HSCT recipients remains challenging as there are many possible infectious and noninfectious causes for fever in these patients. In view of rising antimicrobial resistance in hematology patients, ECIL issued guidelines in 2011 introducing the concept of escalation/de-escalation of empirical therapy and suggesting discontinuation of broad-spectrum antibiotic therapy under certain conditions, which has been confirmed safe in several recent publications [4][5][6][7][8][9]. Compliance with these recommendations has never been assessed and this survey was performed to quantify their current implementation rate in EBMT centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of febrile neutropenia in HSCT recipients remains challenging as there are many possible infectious and noninfectious causes for fever in these patients. In view of rising antimicrobial resistance in hematology patients, ECIL issued guidelines in 2011 introducing the concept of escalation/de-escalation of empirical therapy and suggesting discontinuation of broad-spectrum antibiotic therapy under certain conditions, which has been confirmed safe in several recent publications [4][5][6][7][8][9]. Compliance with these recommendations has never been assessed and this survey was performed to quantify their current implementation rate in EBMT centers.…”
Section: Discussionmentioning
confidence: 99%
“…This led the European Conference on Infections in Leukemia (ECIL) to issue guidelines suggesting strategies of de-escalation and discontinuation of broad-spectrum antibiotic therapy under certain conditions [6]. The safety of de-escalation/discontinuation strategies prior to neutrophil recovery in high risk patients has been confirmed in several publications [7][8][9]. A recent critical appraisal on the use of fluoroquinolone prophylaxis (FP) concluded that the possible benefits on lowering the rate of bloodstream infections should be weighed against its impact in terms of toxicity and risk of increased colonization/infection with fluoroquinolone or multidrug resistant strains [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these prior studies were conducted in Europe, thus limiting the applicability of the results to patients in the United States in which clinical practices may vary. [10][11][12] Among the studies conducted in the United States, the study by Kroll et al 13 had a smaller sample size, did not include HCT recipients, and the minimum duration of BSA was 14 days, and in the study by Snyder et al, 14 haploidentical and autologous HCT recipients were excluded. Another distinction from prior studies in terms of statistical analysis was the use of a multivariate logistic regression model adjusted for confounding variables to estimate AORs for rates of recurrent fever, re-escalation of therapy, and CDI.…”
Section: Discussionmentioning
confidence: 99%
“…However, the safety of this de-escalation approach has not been extensively studied within the United States as most prior studies were conducted in Europe, and among the studies conducted in the United States, autologous and haploidentical HCT recipients were excluded. [10][11][12][13][14] The purpose of this study was to evaluate the outcomes associated with early de-escalation of BSA prior to hematopoietic recovery in autologous and allogeneic HCT recipients with FN of unknown origin.…”
Section: Introductionmentioning
confidence: 99%
“…Current guidelines recommend that among neutropenic patients with clinical or microbiologically documented infection, antibiotics be continued for at least the duration of neutropenia [3]. Recent studies exploring outcomes among high-risk neutropenic patients undergoing de-escalation before resolution of neutropenia showed shorter duration of antibiotics without an increase in mortality [4, 5]. However, neither of these studies was powered to primarily assess differences in mortality.…”
mentioning
confidence: 99%